Lewinnek zone not “the be-all and end-all” functional planning for acetabular component positioning in total hip arthroplasty - Raffaele Iorio; Edoardo Viglietta; Federico Corsetti; Yuri Gugliotta; Carlo Massafra; Daniele Polverari; Andrea Redler; Nicola Maffulli (Arthroplasty)
Abstract Background Proper positioning of a total hip arthroplasty (THA) plays a crucial role in the success and long-term survivorship of the implant. Cup positioning within the Lewinnek Safe Zone (LSZ) does not, however, avoid implant dislocation. Thus, the concept of a functional cup position has been introduced. The purpose of this study was to assess the discrepancy between LSZ and the acetabular cup position suggested by the patient’s specific functional planning. The hypothesis was that a mismatch does exist. Methods One hundred consecutive patients with primary hip osteoarthritis undergoing primary THA with a personalized functional preoperative planning and patient-specific cup implantation system were enrolled. Anatomical and spino-pelvic functional parameters were recorded and, for each patient, a “safe cup orientation” was suggested. The suggested functional safe zone was compared to the LSZ. Results The mean suggested inclination was 39° ± 3° (range 32°–45°). The mean suggested anteversion was 21° ± 3° (range 12°–28°). The patient’s functional acetabular inclination (AI) corresponded to the LSZ in one of the 100 patients, whereas the acetabular anteversion (AV) was outside the LSZ in 8 of the 100 patients. The mean pelvic tilt while standing and sitting were 0.5° ± 7° (range 21°–45°) and −6° ± 16.7° (range −63°–33°), respectively. The mean pelvic incidence was 52° ± 9.7° (range 33°–83°). Conclusion When a functional patient’s specific preoperative planning is performed, the LZS does not correspond to the patient’s functional safe zone in about 8% of patients. The concept of a universal safe zone should be revisited, and a functional personalized safe zone may have to be more widely considered.